The Clinical Features of FLAIR-Hyperintense Lesions in Anti-MOG Antibody Associated Cerebral Cortical Encephalitis with Seizures: Case Reports and Literature Review - Wang, Yun-feng; Liu, Xue-wu; Lin, Jian-ming; Liang, Ji-ye; Zhao, Xiu-he; Wang, Sheng-jun (Frontiers in Immunology, 2021)
Background The presence of fluid attenuated inversion recovery (FLAIR)-hyperintense lesions in anti-myelin oligodendrocyte glycoprotein (MOG) antibody-associated cerebral cortical encephalitis with seizures (FLAMCES) was recently reported. However, the clinical characteristics and outcome of this rare clinico-radiographic syndrome remain unclear. Methods The present study reported two new cases. In addition, cases in the literature were systematically reviewed to investigate the clinical symptoms, magnetic resonance imaging (MRI) abnormalities, treatments and prognosis for this rare clinico-radiographic syndrome. Results A total of 21 cases were identified during a literature review, with a mean patient age at onset of 26.8 years. The primary clinicopathological characteristics included seizures (100%), headache (71.4%), fever (52.3%) and other cortical symptoms associated with the encephalitis location (61.9%). The common seizure types were focal to bilateral tonic-clonic seizures (28.6%) and unknown-onset tonic-clonic seizures (38.1%). The cortical abnormalities on MRI FLAIR imaging were commonly located in the frontal (58.8%), parietal (70.6%) and temporal (64.7%) lobes. In addition, pleocytosis in the cerebrospinal fluid was reported in the majority of the patients (95.2%). All patients received a treatment regimen of corticosteroids and 9 patients received anti-epileptic drugs. Clinical improvement was achieved in all patients; however, one-third of the patients reported relapse following recovery from cortical encephalitis. Conclusions FLAMCES is a rare phenotype of MOG-associated disease. Thus, the wider recognition of this rare syndrome may enable timely diagnosis and the development of suitable treatment regimens.